Principals’ Delegation of Functions and Teachers’ Job Performance Amidst Covid-19 Pandemic in Public Senior Secondary Schools - Olaifa, Adeseko Sunday; Sani, Lauratu Haruna; Olaifa, Ebunlomo Oreoluwa; Adeoye, Moses Adeleke (Jurnal Pedagogi dan Pembelajaran, 2024)
There are a lot of impact of the COVID-19 pandemic on principals' delegation functions and teachers' job performance in a public Senior Secondary school. The study aimed to analyze the level at which principals delegate functions to teachers, the relationship between principals' delegation function techniques and teacher job performance, and the factors that hinder effective delegation practices. A descriptive survey research design was used with 1604 teachers and principals from 38 public secondary schools. Four research questions were raised to guide the study. Data collection was conducted using a self-structured questionnaire. The results showed that principals used various delegation functions and techniques during the pandemic, such as delegating departmental heads to monitor teachers' performance, assigning form masters to enforce school rules, directing heads of departments to mark lesson notes, cross-checking teachers' comments on student report cards, demanding reports from parent-teacher associations, and cross-checking departmental head teachers' classroom attendance books. These delegation functions and techniques were found to be effective in enhancing teachers' morale, meeting curriculum outlines, and achieving educational goals. The pandemic has driven the need for adaptable school leadership, and the efficiency of principals' delegation functions must be improved to boost teacher morale and ensure the achievement of educational goals.